MENYELAMATKAN REMAJA DARI BAHAYA LGBT DENGAN PENDAMPINGAN, PENGENALAN DAN PENDIDIKAN SEKS DI PONDOK PESANTREN SUMATERA BARAT - Mellyarti Syarif; Meri Susanti (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
The age of teenagers who are full of jolts is the gateway to early adulthood, this period brings them to drastic changes, physically and psychologically. Psychological changes make adolescents experience the following things "emotions are unstable, start and easily attracted to the opposite sex, great curiosity, do not want to depend on parents", Elly Risman, et al (2014: 7). These changes make them unstable and easily affected by the environment, both positive and negative. Teenagers have several developmental tasks, one of which is to build relationships with peers, especially with the opposite sex. According to Ericson in Taufik, the most dominant development in adolescence is sex-related things, James Hansens in Taufik (2009: 71). Environment, peers can give positive and negative colors to sex development. Sexual deviation is known as LGBT (Lesbian, Gay, Bisexual and Transgender).